DNA Damage Repair in Brain Tumor Immunotherapy - Zhao, Shihong; Xu, Boya; Ma, Wenbin; Chen, Hao; Jiang, Chuanlu; Cai, Jinquan; Meng, Xiangqi (Frontiers in Immunology, 2022)
With the gradual understanding of tumor development, many tumor therapies have been invented and applied in clinical work, and immunotherapy has been widely concerned as an emerging hot topic in the last decade. It is worth noting that immunotherapy is nowadays applied under too harsh conditions, and many tumors are defined as "cold tumors" that are not sensitive to immunotherapy, and brain tumors are typical of them. However, there is much evidence that suggests a link between DNA damage repair mechanisms and immunotherapy. This may be a breakthrough for the application of immunotherapy in brain tumors. Therefore, in this review, first, we will describe the common pathways of DNA damage repair. Second, we will focus on immunotherapy and analyze the mechanisms of DNA damage repair involved in the immune process. Third, we will review biomarkers that have been or may be used to evaluate immunotherapy for brain tumors, such as TAMs, RPA, and other molecules that may provide a precursor assessment for the rational implementation of immunotherapy for brain tumors. Finally, we will discuss the rational combination of immunotherapy with other therapeutic approaches that have an impact on the DNA damage repair process in order to open new pathways for the application of immunotherapy in brain tumors, to maximize the effect of immunotherapy on DNA damage repair mechanisms, and to provide ideas and guidance for immunotherapy in brain tumors.